Domestic politics and international human rights tribunals : the problem of compliance the problem of compliance - Hillebrecht, Courtney (New York, NY : Cambridge University Press, 2014)
Brings together theories of compliance from international law, human rights, and international relations to explain the increasingly important phenomenon of states' compliance with human rights tribunals' rulings.
Human rights tribunals and the challenge of compliance -- Explaining compliance with human rights tribunals -- Domestic institutions and patterns of compliance -- Compliance as a signal of states' human rights commitments : Uribe's Columbia -- Leveraging international law's legitimacy to change policies: -- The bitter pill of compliance: preferences for human rights, democracy, and the rule of law -- Compliance failures: Russia, Italy and Brazil and the politics of non-compliance -- Conclusion: the European and Inter-American courts in context.
Includes bibliographical references and index.
Keywords: Inter-American Court of Human Rights; European Court of Human Rights; Inter-American Court of Human Rights; European Court of Human Rights; International human rights courts -- Political aspects; International and municipal law -- Political aspects; International human rights courts -- Europe; International human rights courts -- Latin America; LAW -- International; Electronic books